Determinants of Quality Jobs Among Youth: An Empirical Investigation Across Occupations in Lagos, Nigeria - Adeosun, Oluyemi Theophilus; Adegbite, Waliu Mulero (Research in Social Sciences and Technology, 2024)
Quality jobs, a multidimensional construct, have been perceived differently in labour management literature. The view that the quality of earnings is the primary determinant of job quality has been criticized. This study, therefore, investigates the characteristics and major factors determining quality jobs among the youths in Lagos, Nigeria. Leveraging on the rational actor theory, Maslow's theory of needs, and Amartya Sen’s capability approach, four hundred (400) employees, mainly youths, across occupational sectors within Lagos, Nigeria, were sampled. Using descriptive statistics and exploratory factor analysis, the study revealed that though wage (quality of earning) is an essential factor determining youths’ perception of a job, findings revealed other vital factors that youths consider in determining quality jobs. The work environment, dignity, and workers’ protection, among others, are identified in this study as determinants of quality jobs. Far-reaching implications, both practical and policy-oriented, emerged for all stakeholders.